KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN DAN SILABUS KURIKULUM 2013 ABAD 21 MELALUI KEGIATAN IN HOUSE TRAINING DI SMP BUDI DARMA KOTA BEKASI - Titi Kurnia Fitriati (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2021)
This study aims to: 1) To find out the steps of implementing In House Training activities in the Preparation of Learning Implementation Plans and Syllabus of the 21st Century 2013 Curriculum to improve the professional competence of teachers in implementing learning. 2) To find out the improvement of teacher competence in the Preparation of Learning Implementation Plans through In House Training activities. The subjects of this study were all teachers of SMP Budi Darma Bekasi City. This research is a School Action Research covering the stages of planning, implementation, observation, and reflection. The research was conducted at Budi Darma Junior High School, Bekasi City. The data analysis technique used is comparative descriptive. The results of the study can be concluded that: 1) The steps for implementing In House Training in order to improve the professional competence of teachers in the Preparation of Learning Implementation Plans at SMP Budi Darma Bekasi City are by conveying, preparing to teachers about the preparation of Learning Implementation Plans with In House Training without disturbing Learning Activities; and 2) In House Training can improve the professional competence of SMP Budi Darma Bekasi City teachers in preparing Learning Implementation Plans, this is indicated by the increasing professional competence of teachers both in the preparation and implementation stages.